An Intrusion Detection System against RPL-based Routing Attacks for IoT Networks - Manjula Hebbaka Shivanajappa; Roopa Maidanahalli Seetharamaiah; Bharath Viswaraju Sai; Arunalatha Jakkanahally Siddegowda; Venugopal Kuppanna Rajuk (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The significant improvement in the Internet, Internet of Things (IoT), communication, and cloud computing have created considerable challenges in providing security for data and devices.  In IoT networks, “Routing Protocol for Low power and Lossy networks”- (RPL) is a communication protocol that enables devices to exchange information and communicate with limited resources like low processing capabilities, less memory and energy. Through the Internet, unauthorised users can access RPL-based IoT networks, making these networks susceptible to routing attacks. Therefore, it is crucial to design Intrusion Detection System-(IDS) to address attacks from IoT communication devices. In this paper, we have proposed GCNConv, a Graph Neural Network (GNN) method that allows capturing the edge and node features of a graph to identify routing attacks. The proposed   system   has experimented on the RADAR dataset and experimental findings proved that, our approach performs well compared to state-of-the-art method with reference to precision, F1-score, accuracy and recall.